Indonesian Capital Market Efficiency: Islamic vis-a-vis Conventional - Abdul Qoyum; Milzamulhaq Mardiya; Muhammad Rizky Prima Sakti (Universitas Islam Negeri Raden Mas Said Surakarta, 2017)
Capital market efficiency is one of the most important part in finance theory, in which assume the price of stock will fully reflect the information available in the market, hence the price will adjust directly and quickly. The objective of this study is to evaluate the efficiency of both Islamic and conventional stock markets, particularly in case of Indonesia. Event study of King Salman Visit in Indonesia was used as testing periods. Abnormal return and average abnormal trading volume activity of 30 companies listed in Jakarta Islamic Index (JII) to represent Islamic capital market and 17 companies listed in LQ45 to represent conventional capital market were employed to explain this issue. The result shows that from abnormal return perspectives both Islamic and conventional capital market are efficient. While from abnormal trading volume activities, shows that during the visit of King Salman, the trading activity in Islamic capital market is increased significantly rather than conventional counterpart.Â Keywords: Islamic capital market, capital market efficiency, abnormal return and abnormal trading volume activityÂ